PERAN HIDDEN CURRICULUM DALAM PEMBENTUKAN AKHLAKUL KARIMAH PESERTA DIDIK - Acip; Nurhasanah (al-Afkar, Journal For Islamic Studies, 2022)
THE ROLE OF THE HIDDEN CURRICULUM IN THE ESTABLISHMENT OF STUDENTS' CHARACTERISTICS Hidden Curriculum refers to the practices and outcomes of the learning process that are not described in the formal curriculum, but are able to have a major influence on the achievement of educational goals. The hidden curriculum also refers to the distribution of norms, belief values ​​that are reflexively conveyed by the teacher both in the learning process and during social interactions within school institutions. This study aims to describe the role of the hidden curriculum in the formation of the morality of students at MAN 2 Sukabumi. The method used in this research is descriptive qualitative research with the type of case study research. The research results show that: (1). The existence of a hidden curriculum that applies at MAN 2 Sukabumi through habituation, order, exemplary educators, and adequate SARPRAS, (2). Hidden curriculum plays a very important role in shaping the morals of students at MAN 2 Sukabumi